PENERAPAN COOPERATIVE LEARNING DENGAN TEKNIK âGAMEâ UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPA - Rojih, Zainur (WAHANA PEDAGOGIKA, 2016)
This research aimed to improve the learning achievement through Cooperative Learning with the technique of "Game". This classroom action research conducted in the first state Junior High School Kalitengah, Lamongan with the research subjects were the ninth E graders in the academic year of 2015/2016. There was three instruments minimum to collect the data that are (1) observation sheet, (2) questionare sheet, and (3) test sheet. The data from observation and questionnaire then was analyzed quantitative descriptively, it means that the description of the learning success was drawn by the increase of the average score of the class. The result showed that the studentsâ achievement in the first cycle (68.67), in the second cycle (74.89), in the third cycle (82.78). Thus, the implementation of cooperative learning with the technique of "game" could improve the studentsâ achievement.